Denial of coevalness: charges of dogmatism in the nineteenth-century humanities. Issue 6 (18th August 2022) - Schep, Caroline; Paul, Herman
ABSTRACT: Since the seventeenth century, scholars have been accusing each other of 'dogmatism'. But what exactly did this mean? In exploring this question, this article focuses on philosophy and Biblical scholarship in nineteenth-century Germany. Scholars in both of these fields habitually contrasted Dogmatismus with Kritik, to the point of emplotting the history of their field as a gradual triumph of critical thinking over dogmatic belief. The article shows that charges of dogmatism derived much of their rhetorical force from such progressive narratives. Especially neo-Kantian philosophers and Biblical scholars of liberal Protestant persuasion liked to depict their opponents as clinging to long-superseded modes of thought, thereby implying that these colleagues harked back to a past from which modern Wissenschaft had emancipated itself. This 'denial of coevalness', as Johannes Fabian calls it, demonstrates to what extent the vice of dogmatism was imbued with normative visions of how the field or, more broadly, German intellectual life should develop.